Analysis of Water Quality Parameters with Plankton Community Structure in Vannamei Shrimp Ponds - Primasari, Kartika; Widodo, Agus (Journal of Information System, Technology and Engineering, 2025)
This study aimed to analyze water quality parameters in relation to the plankton community structure in vannamei shrimp ponds. Observations were conducted from Day of Culture (DOC) 1 to DOC 30 at two pond locations, B6 and B7, focusing on daily measurements of water quality and plankton abundance. Data were analyzed descriptively. The results indicated that water quality parameters generally met optimal standards for vannamei shrimp cultivation, despite natural fluctuations influenced by weather and farming activities. Plankton analysis revealed that both ponds were dominated by the Chlorophyta group, especially Chlorella sp., which reached a maximum abundance of 2,560,000 individuals in pond B6 and 272,500 in pond B7. Biodiversity indices showed stable diversity and low species dominance, indicating a balanced ecosystem. The dominance of Chlorella sp. contributed to the green coloration of pond water and served dual ecological functions: as a natural feed and a photosynthetic agent. Its presence is also beneficial due to its nutritional content, including polysaccharides and vitamin C, which can enhance shrimp immunity. This study confirms the critical role of water quality and plankton composition in maintaining pond productivity and shrimp health in intensive aquaculture systems.